Estudo anatômico comparativo dos músculos da coxa de Cebus spp. (Erxleben, 1777; Primates, Cebidae) - Vieira, Vanessa de Souza (2013)
The objective of this paper to study the anatomy of the thigh muscles of Cebus spp. We used 16 members of eight 8 monkey (Cebus spp.), 7 males and 1 female. For perfusion fixation was performed through the femoral vein of 10% formaldehyde at 5% glycerin. No animals were euthanized for the purposes of this study: four of them suffered accidental deaths in their natural habitat and were donation from Laboratory of Anatomy, Biochemistry, Neuroscience and Behaviour of Primates (LABINECOP) Federal University of Goias, Campus of Catalão, rest of them donation to the Brazilian Institute of Environment and Renewable Natural Resources (IBAMA). It described the origin and insertion of muscles: tensor fascia lata, sartorius, rectus femoris, vastus lateralis, vastus medialis, vastus intermedius, adductor magnus, adductor longus, adductor short, pectineus, gracilis, biceps femoris, adductor cruris caudalis, semitendinosus, semimembranosus own accessory. The thigh muscles of Cebus spp., In general, are more similar to baboons, presumably because both are quadrupeds, submit tail behavior semi-bipedal and arboreal.